Development of calcium alginate beads containing paclitaxel-loaded lipid-core nanocapsules intended for oral administration - Ciocheta, Taiane Medeiro; de Cristo Soares Alves, Aline; Dallemole, Danieli Rosane; Cé, Rodrigo; Stanisçuaski Guterres, Silvia; Raffin Pohlmann, Adriana (Drug Analytical Research, 2026)
We developed a solid formulation of calcium alginate beads containing paclitaxel-loaded lipid-core nanocapsules (PTX-LNC-Bead) intended for oral administration. The PTX-LNC liquid formulation was prepared by interfacial deposition and trapped into calcium alginate beads. These beads were characterized in terms of size, morphology, swelling rate, encapsulation efficiency, and release of PTX and LNC in simulated gastrointestinal fluids. Results showed that the beads were gastro-resistant with low swelling rate and drug release lower than 3.5% at pH 1.2 (2h). At pH 6.8, the beads showed high swelling rate and disintegration after 80 min. Drug release was 60% after 600 min. Particle sizing as a function of time confirmed that LNC were released intact from the beads at pH 6.8 showing that PTX-LNC-Bead is a promising product for PTX oral administration. Our results pave the way for novel formulations intended for drug targeting by the oral route.